Poezija kao prostor intimnog i javnog - Gverić Katana, Petra (Przekłady Literatur Słowiańskich, 2019)
The article gives a brief overview of translated Polish literature in Croatia in 2017 and considers the visibility of Polish poetry in a body of literary works translated after 1990, focusing on contemporary phenomena such as poetry in new media and the place it takes in the contemporary reception.